Interactions of the metal tolerant heterotrophic microorganisms and iron oxidizing autotrophic bacteria from sulphidic mine environment during bioleaching experiments. (1st May 2016) - Jeremic, Sanja; Beškoski, Vladimir P.; Djokic, Lidija; Vasiljevic, Branka; Vrvić, Miroslav M.; Avdalović, Jelena; Gojgić Cvijović, Gordana; Beškoski, Latinka Slavković; Nikodinovic-Runic, Jasmina
Abstract: Iron and sulfur oxidizing chemolithoautotrophic acidophilic bacteria, such as Acidithiobacillus species, hold the dominant role in mine environments characterized by low pH values and high concentrations of reduced sulfur and iron compounds, such as ores, rocks and acid drainage waters from mines. On the other hand, heterotrophic microorganisms, especially their biofilms, from these specific niches are receiving increased attention, but their potential eco-physiological roles have not been fully understood. Biofilms are considered a threat to human health, but biofilms also have beneficial properties as they are deployed in waste recycling and bioremediation systems. We have analyzed interactions of the metal tolerant heterotrophic microorganisms in biofilms with iron oxidizing autotrophic bacteria both from the sulphidic mine environment (copper mine Bor, Serbia). High tolerance to Cu 2+, Cd 2+ and Cr 6+ and the presence of genetic determinants for the respective metal tolerance and biofilm-forming ability was shown for indigenous heterotrophic bacteria that included strains of Staphylococcus and Rhodococcus . Two well characterized bacteria- Pseudomonas aeruginosa PAO1 (known biofilm former) and Cupriavidus metallidurans CH34 (known metal resistant representative) were also included in the study. The interaction and survivability of autotrophic iron oxidizing Acidithiobacillus bacteria and biofilms of heterotrophic bacteria during co-cultivation was revealed. Finally, the effect of heterotrophic biofilms on bioleaching process with indigenous iron oxidizing Acidithiobacillus species was shown not to be inhibitory under in vitro conditions. Highlights: Heterotrophic bacteria from the mining area showed high tolerance to heavy metals. Pseudomonas aeruginosa PAO1 tolerated elevated concentrations Cd 2+, Cr 6+ and Cu 2+ . Biofilms of heterotrophs showed higher tolerance to mixed metals. Biofilms were resistant to low pH and did not affect growth of Acidithiobacillus sp. Biofilms did not affect bioleaching process of Acidithiobacillus sp.